El español como L2 en aprendientes bilingües hablantes de namtrik en edad infantil: estudio de actitudes lingüísticas - Chamorro Mejía, Mónica (Colombian Applied Linguistics Journal, 2021)
The Misak are an indigenous group from southwest Colombia that have managed to keep their linguistic and cultural identity despite a close and long-time historical contact with western culture and with Spanish, the territory’s main language. This article shows the results of a study on linguistic attitudes, which has extrapolated the perceptions of a school-aged Misak children group, 5th grade students, Namtrik native speakers and Spanish as a Second Language learners, regarding some varieties of the spoken Spanish in Colombia, including the Namtrik-marked spoken Spanish variety within the Guambia Reservation. The findings of this research have allowed to establish relations between the linguistic attitudes of the Namtrik children, an instrumental-type motivation and the learning problems in a concrete learning situation, determined by the contact between languages and cultures.